Study of doking molecule flavonoid Coleus amboinicus in TGF-1b receptor and lowering MDA concentration on Cisplatin-induce Wistar Rats - Wida Wahidah Mubarokah; Rondius Solfaine; Lailatul Muniroh (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
The aims of this study is to evaluate molecular docking of flavonoid Coleus amboinicus (CA) extracts in transforming growth factor-1b and lowering MDA concentration on cisplatin-induced in Wistar rat. Eighteen male Wistar rats (Rattus norvegicus), 3 months of age with a body weight (BW) of 150-200 g, were allocated into three groups, with six animals per group. The control group received aquadest (P0), the treatment group were treated with single doses of cisplatin (5 mg/kg bw., ip) (P1) and received 100 mg/kg bw of the CA extracts (P2) respectively for 7 days. Bloods collected for analysis of serum alkaline phospatase (AP), Blood Nitrogen Urea (BUN) and Malondialdehid (MDA) concentrations. The levels of Malondialdehid (MDA) concentrations were analysed by Avidin-Horseradish Peroxidase (HRP) Sandwich-ELISA. All groups were sacrified for histopathology. Coleus amboinicus extract significantly decreased the level of AP, BUN and MDA concentrations compared to the control group (p<0.05). The level of MDA could be detected by its level significantly decreased in CA treatment group (p<0.05). Coleus amboinicus (CA) extract has a flavonoid as a marker compound of CA extract has stronger bind to the TGF-β1receptor than its of 3WA_601 ligand in silico analyzed. In histopathological examination showed that cisplatin-induced could alter severe multifocal hemorrhage, interstitial congestion, cell inflammatory, acute glomerular and tubular injury with necrotic cells. Immunohistochemical staining labeled with TGF-1β monoclonal antibodies (Mab) showed marked expression of brownish color aggregates on the surface of tubular epithelial cells and around glomerular mesangial cells in the CA treatment group. This study was concluded that CA extract is inhibited renal tissue injuries by lowering MDA and increasing TGF-1b expression on cisplatin-induced rats. Flavonoid as marker of CA extract has stronger bind to TGF-1b receptor by in silico.